SEDIMENTOLOGY, STRATIGRAPHY AND MICROPALEONTOLOGY OF THE TRIASSIC EVAPORITIC SEQUENCE IN THE SUBSURFACE OF THE BOCCHEGGIANO AND IN SOME OUTCROPS OF SOUTHERN TUSCANY (ITALY) - ROSSANA MARTINI; ANNA GANDIN; LOUISETTE ZANINETTI (Rivista Italiana di Paleontologia e Stratigrafia, 2018)
The Burano Formation, consisting of evaporitic-dolomitic horizons, has been encountered partly in boreholes and partly as scattered outcrops in Boccheggiano and southern Tuscany areas. In the boreholes, this unit overlies the Filladi di Boccheggiano Formation and is overlain by the Calcare Cavernoso or the Ligurian Nappe. In outcrops, this evaporitic-dolomitic sequence, following sulphate dissolution, is represented by the brecciated unit known as Calcare Cavernoso. Sedimentological, micropaleontological and stratigraphical analyses have allowed to assign a Carnian-Norian age to the Burano Formation in southern Tuscany.